Early Microcirculatory Hemodynamic Changes Are Correlated With Functional Outcomes at Discharge in Patients With Aneurysmal SAH - Wen, Lili; Zhou, Longjiang; Wu, Qi; Tang, Xiaoyu; Ge, Jiajia; Zhou, Xiaoming; Zhang, Xin (Frontiers in Neurology, 2022)
Purpose The technique of color-coding blood flow analysis was used to explore the correlation between the microcirculatory hemodynamic changes on digital subtraction angiography (DSA) images in patients with aneurysmal subarachnoid hemorrhage (SAH) at the early stage and functional outcomes at discharge. Methods Data of 119 patients who underwent DSA examination due to SAH were retrospectively analyzed. The following hemodynamic parameters of the four region of interests (ROIs) [an ophthalmic segment of the internal carotid artery (ICA), frontal and parietal lobe, and superior sagittal sinus] were analyzed: the time-to-peak (TTP), the area under the curve (AUC), the full width at half maximum (FWHM), mean transit time (MTT), and circulation time. Multifactor regression analysis was performed to explore the correlation between the hemodynamic parameters and functional outcomes in patients at discharge. Results Of 119 patients with SAH, good and poor outcomes were found in 83 (69.7%) and 36 (30.3%) patients, respectively. The hemodynamic parameters including the FWHM, relative TTP (rTTP), and circulation time were significantly correlated with the Hunt–Hess grade (p < 0.005, p = 0.03, and p < 0.005) and the World Federation of Neurological Societies Scale grade (p < 0.005, p = 0.02, and p = 0.01). The FWHM was significantly prolonged with the increase of modified Fisher grade (p = 0.02). The multifactor analysis showed that the FWHM [odds ratio (OR) 17.56, 95% CI: 1.13–272.03, p = 0.04] was an independent risk factor predicting the functional outcomes in patients at discharge. Conclusion The technique of color-coding blood flow analysis could be suitable for the qualified evaluation of disease conditions at an early stage of SAH as well as the prediction of outcomes.